2003
DOI: 10.1023/a:1023935605864
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Triacylglycerol (TAG) is the major carbon storage reserve in oilseeds such as Arabidopsis. Acyl-CoA:diacylglycerol acyltransferase (DGAT) catalyses the final step of the TAG synthesis pathway. Although TAG is mainly accumulated during seed development, and DGAT has presumably the highest activity in developing seeds, we show here that TAG synthesis is also actively taking place during germination and seedling development in Arabidopsis. The expression pattern of the DGAT1 gene was studied in transgenic plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The 4CL metabolizes p-coumaric acid and ferulic acid to monolignols (Gross and Zenk, 1974). DGOAT is most probably involved in the esterification of glycerol compounds into aliphatic suberin precursors in roots (Cases et al, 1998; Lu et al, 2003), to which ferulic acid is transferred by aliphatic suberin feruloyl transferase (Molina et al, 2009) to generate suberin monomers. These observations suggest that the formation of monolignols in the OE mutant was reduced, whereas the pathway to suberin monomers was enhanced, leading to the speculation that suberin monomers are the substrate of the OE ABC transporter OsABCG25 ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 4CL metabolizes p-coumaric acid and ferulic acid to monolignols (Gross and Zenk, 1974). DGOAT is most probably involved in the esterification of glycerol compounds into aliphatic suberin precursors in roots (Cases et al, 1998; Lu et al, 2003), to which ferulic acid is transferred by aliphatic suberin feruloyl transferase (Molina et al, 2009) to generate suberin monomers. These observations suggest that the formation of monolignols in the OE mutant was reduced, whereas the pathway to suberin monomers was enhanced, leading to the speculation that suberin monomers are the substrate of the OE ABC transporter OsABCG25 ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first time that the induction of DGAT2 has been reported in seedling tissues. Transcriptional analysis in Arabidopsis seedlings has revealed high mRNA levels of type-1 DGAT during the post-embryonic stages in both cotyledons and hypocotyls (Lu et al , 2003) and DGAT1 activity has been previously correlated with de novo TAG synthesis in the cotyledons of castor seedlings (He et al , 2006). It is likely that excess sugar production is channelled into TAGs for internal use or for storage to prevent osmotic effects (He et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Both TAG accumulation and DGAT activity have been reported in several other organs, such as flowers, developing siliques, germinating seeds, young seedlings, and senescing leaves of Arabidopsis (Zou et al , 1999; Kaup et al , 2002), and in stems, flowers, roots, and leaves of tobacco (Zhang et al , 2005). Based on those observations, it has been suggested that TAG may also be implicated in physiological roles other than as a carbon or energy source (Lu and Hills, 2002; Lu et al , 2003). …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, because the Arabidopsis DGAT1 mutant AS11 shows only a 30-35% decrease in oil content [6,9], it was apparent that other enzymes must contribute to oil synthesis in the developing seed [22]. Thus, an examination of the contribution of DGAT2, PDAT2 or PDAT1 to oil deposition in an AS11 background was studied by performing double mutant crosses with AS11 [17].…”
Section: Introductionmentioning
confidence: 99%